Energy Efficient Compressive Sensing based Multi-focus Image Fusion Scheme for WVSN - Subbu Lakshmi, TC; Gnanadurai, D; Muthulakshmi, I (International Journal of Computer Sciences and Engineering, 2025)
Wireless Visual Sensor Networks (WVSN) is the enhanced version of WSN that captures and processes visual data from the environment. Owing to the numerous advantages, the WVSN is widely applicable in several real-time applications. The main considerations of WVSN are energy efficiency and quality. This work intends to propose an energy efficient compressive sensing based multi-focus image fusion scheme for WVSN. The image fusion is carried out by contourlet and curvelet, as these have multi-scale and multi-directional properties. The image fusion rule is framed by considering the energy of the pixels. Finally, the image reconstruction is carried out by CoSaMP (Compressive Sampling Matching Pursuit) algorithm. The performance of the proposed approach is tested in terms of image quality, energy and time consumption and the results are compared with the existing approaches. The proposed image fusion scheme outperforms the existing approaches, while proving better quality.